BUKU TUTORIAL PEMBUATAN WAYANG BEBER KERTAS KORAN UNTUK MENDUKUNG PROGRAM EKONOMI KREATIF DI SURAKARTA - Zarkasi, Much Sofwan (Acintya, 2014)
The making of books tutorial how to make a work of art wayang beber of newsprint material on thiscanvas is an effort to support government programs Surakarta creative economy in this case is aproduct development process featured art made from paper craft paper which functioned as souvenirsSurakarta . Book a tutorial how to make a work of art wayang beber of newsprint material onthis canvas that is expected to be read and studied community craftsmen made of old newspapers inSurakarta.Keywords: tutorial book, wayang beber, newspaper